Implementation of global health competencies: A scoping review on target audiences, levels, and pedagogy and assessment strategies. - Meike Schleiff; Bhakti Hansoti; Anike Akridge; Caroline Dolive; David Hausner; Anna Kalbarczyk; George Pariyo; Thomas C Quinn; Sharon Rudy; Sara Bennett (PLoS ONE)
Background As the field of global health expands, the recognition of structured training for field-based public health professionals has grown. Substantial effort has gone towards defining competency domains for public health professionals working globally. However, there is limited literature on how to implement competency-based training into learning curricula and evaluation strategies. Objectives This scoping review seeks to collate the current status, degree of consensus, and best practices, as well as gaps and areas of divergence, related to the implementation of competencies in global health curricula. Specifically, we sought to examine (i) the target audience, (ii) the levels or milestones, and (iii) the pedagogy and assessment approaches. Sources of evidence A review of the published and grey literature was completed to identify published and grey literature sources that presented information on how to implement or support global health and public health competency-based education programs. In particular, we sought to capture any attempts to assign levels or milestones, any evaluation strategies, and the different pedagogical approaches. Results Out of 68 documents reviewed, 21 documents were included which contained data related to the implementation of competency-based training programs; of these, 18 were peer-reviewed and three were from the grey literature. Most of the sources focused on post-graduate public health students, professional trainees pursuing continuing education training, and clinical and allied health professionals working in global health. Two approaches were identified to defining skill level or milestones, namely: (i) defining levels of increasing ability or (ii) changing roles across career stages. Pedagogical approaches featured field experience, direct engagement, group work, and self-reflection. Assessment approaches included self-assessment surveys, evaluations by peers and supervisors, and mixed methods assessments. Conclusions The implementation of global health competencies needs to respond to the needs of specific agencies or particular groups of learners. A milestones approach may aide these efforts while also support monitoring and evaluation. Further development is needed to understand how to assess competencies in a consistent and relevant manner.